Looking Forward: The Promise of Widespread Implementation of Parent Training Programs. (November 2013) - Forgatch, Marion S.; Patterson, Gerald R.; Gewirtz, Abigail H.
Over the past quarter century, researchers have developed a body of parent training programs that have proven effective in reducing child behavior problems, but few of these have made their way into routine practice. This article describes the long and winding road of implementation as applied to children's mental health. Adopting Rogers' (1995) diffusion framework and Fixsen and colleagues' implementation framework (Fixsen, Naoom, Blase, Friedman, & Wallace, 2005), we review more than a decade of research on the implementation of Parent Management Training—Oregon Model (PMTO). Data from U.S. and international PMTO implementations are used to illustrate the payoffs and the challenges of making empirically supported interventions routine practice in the community. Technological advances that break down barriers to communication across distances, the availability of efficacious programs suitable for implementation, and the urgent need for high quality mental health care provide strong rationales for prioritizing implementation. Over the next quarter of a century, the challenge is to reduce the prevalence of children's psychopathology by creating science-based delivery systems to reach families in need, everywhere.